Keberadaan Hukum Sebagai Instrument Perubahan Sosial Dalam Konflik Pengadaan Tanah Bagi Pembangunan Yang Berkeadilan dan Berkelanjutan - Wahyu Apria Ningrum; Ajeng Nur Annisa; Anggia Nur Ramadhani D. (HUKMY : Jurnal Hukum, 2025)
This study focuses on the existence of law as an instrument of social change in land acquisition. The background that can be found in community life, law is often understood as an effort to seek justice. Reviewing the existence of law in community life, if we look at the case of land acquisition in Indonesia, it often causes endless conflicts for that, there are problems that will be studied more deeply regarding the function of law as an instrument of social change in resolving land acquisition conflicts for the public interest, the role of law in resolving unlawful acts that occur in land acquisition conflicts for the public interest and the role of society in the process of land acquisition for development in the public interest.